Clot formation, lysis and ultrastructure in patients with acute phase myocardial infarction. (25th November 2020) - Siniarski, A; Baker, S.R; Duval, C; Gajos, G; Nessler, J; Ariens, R.A.S
Abstract: Background/Introduction: Patients with established coronary artery disease have impaired clot structure and lysis. Prior research has compared patients with myocardial infarction to those with stable coronary artery disease (without a healthy reference), or patients after myocardial ischemia. The role of clot structure in the acute phase of the disease is unknown. Purpose: Investigate clot structure in the acute phase of myocardial infarction (AMI) compared to healthy controls. Methods: Plasma clots from AMI patients (within 12 hours of symptoms onset) or healthy controls were analyzed by turbidity and lysis. Clot pore size was determined by permeation. Clot ultrastructure was determined by confocal and scanning electron microscopy. Average fiber radius and protofibril packing were investigated by turbidimetry. Results: Analysis on clot formation, using turbidity, showed increased lag time (24%, p<0.05), suggesting changes in protofibril packing and increased fiber size for AMI patients compared to controls. Additionally, AMI clots formed more quickly as evidenced by average rate of clotting (2.9-fold increase, p<0.001) and time to maximum absorbance (38% decrease, p<0.0001). Decreased plasminogen in AMI patients (23%, p<0.05) had strong effects on clot lysis, including increased time to half lysis (1.72-fold, p<0.0001) and increased time to maximum lysis rate (7.96-fold, p<0.0001). Taken together, these results suggest that AMI patients form less porous clots made from densely packed fibers with decreased numbers of protofibrils, which was confirmed using permeation (1.05-fold decrease, p<0.0001), confocal (Figure 1) and scanning electron microscopy (46% increase, p<0.0001), and turbidimetry (16% decrease, p<0.05) respectively. Conclusions: Plasma from patients with AMI form denser and less permeable clots that lyse more slowly than healthy controls. These data show marked abnormalities in clot ultrastructure that contribute to the high risk of thrombosis during the acute phase of myocardial infarction, which has not shown in previous investigations. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Jagiellonian University Medical College to G.G. (N41/DBS/000096) and BHF Programme Grant to S.R.B. and R.A.S.A. (RG/18/11/34036).